2018
DOI: 10.1186/s12859-018-2353-5
|View full text |Cite
|
Sign up to set email alerts
|

XenofilteR: computational deconvolution of mouse and human reads in tumor xenograft sequence data

Abstract: BackgroundMouse xenografts from (patient-derived) tumors (PDX) or tumor cell lines are widely used as models to study various biological and preclinical aspects of cancer. However, analyses of their RNA and DNA profiles are challenging, because they comprise reads not only from the grafted human cancer but also from the murine host. The reads of murine origin result in false positives in mutation analysis of DNA samples and obscure gene expression levels when sequencing RNA. However, currently available algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 33 publications
0
123
0
Order By: Relevance
“…As PDX tumors grow, their human tumor stroma is replaced by mouse stroma [48]. In our comparison of transcriptomes of original brain metastasis from one patient and its xenografts in mouse brain and MFP, we observed that approximately 15% of RNA transcripts of PDXs were murine.…”
Section: Discussionmentioning
confidence: 85%
“…As PDX tumors grow, their human tumor stroma is replaced by mouse stroma [48]. In our comparison of transcriptomes of original brain metastasis from one patient and its xenografts in mouse brain and MFP, we observed that approximately 15% of RNA transcripts of PDXs were murine.…”
Section: Discussionmentioning
confidence: 85%
“…Whole-genome sequence reads from EuroPDX BRCA tumors and corresponding tumor grafts at different passages were mapped to the reference human genome (GRCh38) and mouse genome (GRCm38/mm10, Ensembl 76) using Burrows-Wheeler Aligner (BWA) v0.7.15. Subsequently, mouse reads were excluded with XenofilteR 32 . Other processing steps are similar as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Bioinformatics analyses have recently been developed to distinguish human‐specific results from mixed human and mouse results. By using this approach, the possible contamination of results can largely be avoided . Moreover, considering the accumulated changes in xenograft tumors, PDX models do not reliably preserve the original information of parental tumors upon serial transplantation.…”
Section: Conclusion and Perspectivementioning
confidence: 99%